2010
DOI: 10.1007/s13239-010-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on PEG Integrated Alginate–Chitosan Microcapsules for Myocardial Therapy Using Marrow Stem Cells Genetically Modified by Recombinant Baculovirus

Abstract: Bone marrow derived mesenchymal stem cell (BMSCs) therapy can significantly improve cardiac ventricular function following ischemic injury. Their potential can be further enhanced by using genetically modified cells, overexpressing certain therapeutic biomolecules. However, such therapy is limited by low efficiency of transplantation of the cells, secreting inadequate therapeutic proteins. To address these issues, we developed recombinant baculoviruses to genetically modify the BMSCs and investigated the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Hence, current research is highly focused on developing an efficient delivery system that can successfully transplant a sufficient number of stem cells at the desired site with higher retention and minimal biological loss or immune response. Some of our more recent work has shown that retention can be increased by four folds in the heart by using biocompatible polymeric alginate microcapsules as a delivery system, which can, in turn, help in functional recovery of acutely infarcted heart [ 59 61 ].…”
Section: Emerging Role Of Bmscs For Cell and Tissue Regeneration Tmentioning
confidence: 99%
“…Hence, current research is highly focused on developing an efficient delivery system that can successfully transplant a sufficient number of stem cells at the desired site with higher retention and minimal biological loss or immune response. Some of our more recent work has shown that retention can be increased by four folds in the heart by using biocompatible polymeric alginate microcapsules as a delivery system, which can, in turn, help in functional recovery of acutely infarcted heart [ 59 61 ].…”
Section: Emerging Role Of Bmscs For Cell and Tissue Regeneration Tmentioning
confidence: 99%
“…An improper coating can make the capsular surface charged. Hydrophilic, nonionic, and the inert nature of PEG make it an ideal candidate to neutralize the surface charge and hence increase the immunoprotective potential of the capsules by alleviating the chance of having surface protein adhesions [ 19 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Artificial cell microencapsulation, a concept in which biologically active materials are encapsulated in specialized ultrathin semipermeable polymer membranes, has been proposed here as means to address the above-mentioned problem [ 17 19 ]. These microcapsules provide a large surface area to volume ratio which promotes rapid diffusion of oxygen, nutrients, and waste metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…To induce differentiation, young and old MSCs were first seeded in 24-well plates at a high confluency using serum supplemented DMEM media. After 24 hours of culture, the media were replaced with either osteogenesis induction media or adipogenesis induction media (Millipore, Billerica, MA) to induce differentiation [ 15 , 16 ]. During this period, the induction media were replaced every alternate day with fresh induction media and later, differentiation media according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%